Marketing Strategy Formulation And Implementation At The Garuda Wisnu Kencana Cultural Park To Create Word Of Mouth Marketing - Putra, Raden Muhamad Mersa Satyawardana; Desiana, Krisnati (The Indonesian Journal of Business Administration, 2013)
Krisnati DesianaLocated in Jimbaran, Bali, the Garuda Wisnu Kencana Cultural Park or better known by the locals as GWK with its gigantic Garuda Wisnu statue will serve as Bali's tourism landmark. In this paper the objective of this research is to formulate a Word Of Mouth marketing strategy that will make GWK become larger and better known not just in Indonesia but also around the world.The whole concept is to be a symbol of art and culture. It is projected that GWK Cultural theme Park could become a symbol of international tourism in Indonesia. It will become a tourist destination. The methodology that will be used in this research is Qualitative Research. Qualitative research uses a direct approach that clearly sets forth the purposes of research so the question is simple and straight to the point of the problem, in this case I used the In Depth Interview, ideal for travelers as the target of my respondents. Results that can be achieved will be used as guidelines for the GWK management to be better. Before doing what was described above, it is better for the leadership of the Garuda Wisnu Kencana Cultural Park to conduct internal management primarily about being more modern. It is better to do the research of HR systems as well. Need to do more market research about consumer behavior in the visiting tourist spots.Publication is an important media that needs to be maintained with consistency and content delivery that is direct perception